Geometria de dutos de escape otimizada para aplicação na cogeração da produção de energia elétrica - Gomes, Pedro Henrique Garcia (2017)
The objective of this work is to seek greater efficiency in energy conversion using the Seebeck modules, from the duct geometry optimization exhaust hot gases. Different materials and geometries are tested. The duct thickness was varied along the longitudinal fluid flow and optimized parameters are obtained heuristically . After the development of optimized duct model, a prototype is built for testing in the actual system. From the resistive air layer, the surface temperature gradient equalization is obtained, improving the efficiency of the system.